A Common Genetic Origin for Early Farmers from Mediterranean Cardial and Central European LBK Cultures - Olalde, Iñigo (2018)
The spread of farming out of the Balkans and into the rest of Europe followed two distinct routes: An initial expansion represented by the Impressa and Cardial traditions, which followed the Northern Mediterranean coastline; and another expansion represented by the LBK (Linearbandkeramik) tradition, which followed the Danube River into Central Europe. Although genomic data now exist from samples representing the second migration, such data have yet to be successfully generated from the initial Mediterranean migration. To address this, we generated the complete genome of a 7,400-year-old Cardial individual (CB13) from Cova Bonica in Vallirana (Barcelona), as well as partial nuclear data from five others excavated from different sites in Spain and Portugal. CB13 clusters with all previously sequenced early European farmers and modern-day Sardinians. Furthermore, our analyses suggest that both Cardial and LBK peoples derived from a common ancient population located in or around the Balkan Peninsula. The Iberian Cardial genome also carries a discernible hunter-gatherer genetic signature that likely was not acquired by admixture with local Iberian foragers. Our results indicate that retrieving ancient genomes from similarly warm Mediterranean environments such as the Near East is technically feasible.